Molecular pathogenesis of Chlamydia trachomatis - Jury, Brittany; Fleming, Charlotte; Huston, Wilhelmina M.; Luu, Laurence Don Wai (Frontiers in Cellular and Infection Microbiology, 2023)
Chlamydia trachomatis is a strict intracellular human pathogen. It is the main bacterial cause of sexually transmitted infections and the etiologic agent of trachoma, which is the leading cause of preventable blindness. Despite over 100 years since C. trachomatis was first identified, there is still no vaccine. However in recent years, the advancement of genetic manipulation approaches for C. trachomatis has increased our understanding of the molecular pathogenesis of C. trachomatis and progress towards a vaccine. In this mini-review, we aimed to outline the factors related to the developmental cycle phase and specific pathogenesis activity of C. trachomatis in order to focus priorities for future genetic approaches. We highlight the factors known to be critical for developmental cycle stages, gene expression regulatory factors, type III secretion system and their effectors, and individual virulence factors with known impacts.